Design of molecularly imprinted polymers for sensors and solid phase extraction - Subrahmanyam, Sreenath (Cranfield University, 2002)
This thesis presents broadly the applications of molecularly imprinted polymers in sensors and solid phase extraction. Sensors for creatine and creatinine have been reported using a novel method of rational design of molecularly imprinted polymers (MIPs), and solid phase extraction of aflatoxin-B 1 has also been described in the thesis. A method for the selective detection of creataine and creatinine is reported in this thesis, which is based on the reaction between polymerised hemithioacetal, formed by allyl mercaptan, o-phthalic aldehyde, and primary amine leading to the formation of fluorescent isoindole complex. This method was demonstrated for the detection of creatine using creatine-imprinted MIPs. Since MIPs created using traditional methods were unable to differentiate between creatine and creatinine, a new approach to the rational design of a MIP selective for creatinine was developed using computer simulation. A virtual library of functional monomers was assigned and screened against the target molecule, creatinine, using molecular modeling software. The monomers giving the highest binding score were further tested using simulated annealing in order to mimic the complexation of the functional monomers with template in the monomer mixture. The result of this simulation gave an optimised MIP composition. The computationally designed polymer demonstrated superior selectivity in comparison to the polymer prepared using traditional approach, a detection limit of 25 μM and good stability. The 'Bite-and- Switch' approach combined with molecular imprinting can be used for the design of assays and sensors, selective for amino containing substances. MEP for the selective binding properties for aflatoxin-B 1 was prepared using the computational approach. The results obtained demonstrate that the MISPE offers a simple, convenient and a rapid methodology for solid phase extraction of aflatoxin-B 1 even at very low concentrations of 2 ppb. The commercially available C-18 cartridges were able to recover only about 52% of aflatoxin-B 1 at concentrations of 2 ppb when compared with almost complete recovery by the MIP. We have proved here that, MIPs as a solid phase extraction materials offer important and practical advantages with respect to other solid phase extraction methodologies.